Kesigapan Palang Merah Indonesia (PMI) Terhadap Bencana Yang Terjadi di Kota Medan - Nurul Fadillah; Siti Nurhalizah; Muhammad Yasir; Fani Tahria; Usiono Usiono (Peneliti.net, 2023)
This study aims to see how the alertness of the Indonesian Red Cross (PMI) in dealing with the disaster that occurred in the city of Medan. This research was conducted on September 17 2022 at the PMI Medan building. The subjects of this research are people who play a role in the Indonesian Red Cross and some communities. Data collection techniques using observation, interviews and documentation. The approach used in this study is a qualitative approach. The results of the study show that PMI Medan City moves quickly and is responsive when a disaster situation occurs in the city of Medan. This is evident in the results of interviews that have been conducted by several people directly involved in PMI Medan as well as some of the surrounding community. Even though there were several obstacles when they were about to carry out their duties, the Medan City PMI team always tried their best to remain fast and alert in the face of the disaster that occurred. So it can be concluded that the Medan PMI has been alert to the disasters that have occurred in the city of Medan.